Cytotoxic Activity and Secondary Metabolite Characteristics of Sea Cucumber Actinopyga sp. Methanolic Extract - Muhammad Nursid; Afrilia Putri Maharani; Riyanti Riyanti; Endar Marraskuranto (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2016)
The objectives of this research were to assess cytotoxic activity and examine characteristic of sea cucumber Actinopyga sp. methanolic extract. Cytotoxicity assay was conducted using MTT method against WiDr (colon cancer) and T47D (breast cancer) cell lines. Actinopyga sp. methanolic extract was characterized by using phytochemical screening, Transform-Infrared (FT-IR) spectroscopy, dan Liquid Chromatography Ion Trap Time of Flight Mass Spectrophotometer (LC-IT-ToF-MS). The result showed that Actinopyga sp. methanolic extract inhibited Widr and T47D cell lines viability with the IC50 value of 55.93 and 87.55 µg/mL, respectively. Functional groups analysis showed the presence of hydroxyl, amine, carboxylic acid, nitrate, amide, sulphur, ester, and ether. LC-IT-ToF-MS analysis of crude extract showed that it containing many steroids compound.